2021
DOI: 10.1186/s40814-021-00941-w
|View full text |Cite
|
Sign up to set email alerts
|

High-intensity treadmill training and self-management for stroke patients undergoing rehabilitation: a feasibility study

Abstract: Background Physical activity undertaken by stroke survivors is generally low. This trial investigated the feasibility of delivering a high-intensity treadmill and self-management program to people with stroke undergoing inpatient rehabilitation and determine whether physical activity, walking ability and cardiorespiratory fitness could be increased. Method A phase I, single-group, pre-post intervention study was conducted with stroke survivors unde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 53 publications
0
4
0
Order By: Relevance
“…10 Previous studies have found evidence to incorporate post-stroke cardiorespiratory training to improve fitness, balance, speed, and walking ability, and that a cardiorespiratory care program can provide improvements in walking ability and fitness, and when the goal is to improve walking ability after stroke, it is important to consider aerobic capacity training. 9,33,34 The fitness levels in non-community ambulators post stroke can be improved not just by walking but also by graded walking, stationary cycle ergometer, resistance and strength training, among other possibilities. 35 Walking speed is considered a vital sign and an indicator of general health 31 and is important for community integration.…”
Section: Discussionmentioning
confidence: 99%
“…10 Previous studies have found evidence to incorporate post-stroke cardiorespiratory training to improve fitness, balance, speed, and walking ability, and that a cardiorespiratory care program can provide improvements in walking ability and fitness, and when the goal is to improve walking ability after stroke, it is important to consider aerobic capacity training. 9,33,34 The fitness levels in non-community ambulators post stroke can be improved not just by walking but also by graded walking, stationary cycle ergometer, resistance and strength training, among other possibilities. 35 Walking speed is considered a vital sign and an indicator of general health 31 and is important for community integration.…”
Section: Discussionmentioning
confidence: 99%
“…The experimental group received treadmill training and self-management education for 30 min, three times a week for 8 weeks, and usual gait training for 2 days a week. The treadmill training was based on our pilot program 6,7 of up to 30 min walking on a treadmill at an intensity of 40–60% HRR or a Borg Rating of Perceived Exertion 12 of 11–14. Target heart rates were calculated according to the Karvonen method 13 adjusting for beta-blockers.…”
Section: Methodsmentioning
confidence: 99%
“…In piloting this study, we found that treadmill training to this intensity during inpatient rehabilitation is feasible, is not detrimental to walking pattern, and may result in improved walking ability. 6,7 Furthermore, benefits in cardiorespiratory fitness are often only partially maintained beyond the period of intervention. 4 It is therefore important to support stroke International Journal of Stroke, 17 (10) survivors to exercise independently in the long term.…”
Section: Introductionmentioning
confidence: 99%
“…High-Intensity Treadmill Training (HITT) has a positive effect on walking ability, quality of life, cardiorespiratory fitness, compared to Low-Intensity Treadmill Training (LITT) , increased maximal VO2, and the cost of walking in people with chronic stroke [81] . Doing high-intensity exercise on a treadmill as a self-management approach during inpatient rehabilitation can lead to sustained improvement in physical activity, walking ability, fitness, and quality of life [82] . Treadmill exercise with a focus on intensive task-specific training is also a way to facilitate neural plastic brain changes and to strengthen associated motor behavior gains following nerve damage [50] .…”
Section: Overall Physical Activity Improvementmentioning
confidence: 99%